An Analysis of the Governance, Ethical, Legal, and Social Implications of Biocomputing. - Sirbu, Renée A.; Floridi, Luciano (Science & Engineering Ethics, 2026)
Biological computing (biocomputing) leverages biologically derived materials and processes, such as DNA and protein synthesis, to perform computational tasks. Biocomputing offers significant advantages over traditional silicon-based systems in terms of scalability, energy efficiency, computational flexibility, and information storage potential. However, the distinct operational characteristics of biocomputing raise novel governance, ethical, legal, and social implications (GELSI). This article identifies and analyzes key GELSI concerns raised by biocomputing. It then highlights the inadequacies of current regulatory frameworks in addressing the unique challenges posed by massively parallel molecular computations, biosafety risks, probabilistic error management in clinical applications, patentability of biological storage systems, and ownership rights in self-replicating data systems. The analysis concludes by recommending specialized regulatory approaches and international collaboration to govern biocomputing technologies responsibly, ensuring their ethical integration and equitable benefits across global societies.